Implementation of the Value of Unity in Diversity in Elementary Schools - Nurmalia, Nurmalia; Handayani, Kristina; Komariyah, Siti (CV. Rayyan Dwi Bharata, 2023)
Education in Indonesia is heavily influenced by developments in education and technology, the more technology develops, the greater the impact of globalization, therefore we must maintain the value of unity and unity among nations, especially instilling the character of tolerance in elementary schools, so that the nation and state are protected from division. The method used in this research is a literature review, where research results are obtained from books, articles, and journals related to the inculcation of tolerance in diversity in elementary schools and is produced from an analysis of existing theories and has been authentically tested. The purpose of this research is to find out how far the value of unity in diversity is instilled in elementary schools. The results in this study indicate that: (1) Pancasila education becomes character building in the state (2) Pancasila acts as a binder for a sense of unity in diversity among students (3) Diversity in elementary schools becomes learning to deal with diversity in the wider community (4) the value of unity forms a sense of tolerance that can strengthen the unity of the Indonesian nation (5) teaches the value of unity as early as possible to form a character of tolerance that is always inherent in the souls of students.